Reporting and quoting: functional analyses of logico-semantic relations of clause complex citations - Jomaa, Nayef Jomaa; Siti Jamilah Bidin (Penerbit Universiti Kebangsaan Malaysia, 2019)
Citations are significant academically for establishing research backgrounds and justifying a research problem. In spite of the increasing studies on citations, limited studies have employed the Systemic Functional Linguistics in analysing citations. Therefore, this study explores the logico-semantic relations in citations with clause complexes, employing the ideational metafunction of the Functional Theory. The study adopted a purposeful sampling in selecting the literature review chapters of 20 PhD theses by EFL postgraduates in a public Malaysian university in two disciplines: Information Technology and Applied Linguistics. The findings revealed that citations were structured to realise two logico-semantic relations, mainly Expansion and Projection with several subcategories for each. A combination of Projection and Expansion was also used, which resulted in reclassifying the logico-semantic relations. The findings could present comprehensive descriptions of citations that could be pedagogically utilised for academic purposes.